ANALYSIS OF FIELD DISTRIBUTION OF OPTICAL WAVEGUIDE USING LINEAR FINITE ELEMENT METHOD - Mahindra Umbarkar (International Journal of Innovations in Engineering Research and Technology, 2015)
Understanding the propagation properties, the field distribution, and how these depend on the manufacturing parameters is necessary for optimizing optical waveguide performance. The necessity for computer analysis grows as the variety of directing structures and the relying parameters expand and become more complex. Theoretical approaches to waveguide analysis are therefore of great interest. The complex and thorough study of waveguide problems in all dimensions is provided by the Finite Element Method (FEM). The propagation modes of an optical fibre can be calculated using the method shown in this project. The Maxwell equation is reduced to a conventional eigen value equation with symmetric tri-diagonal matrices by finite element method analysis.